TanDEM-X First DEM Acquisition: A Crossing Orbit Experiment - Lopez-Dekker, Paco; Prats, Pau; De Zan, Francesco; Schulze, Daniel; Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Letters, 2011)
This letter describes the first interferometric acquisitions and results obtained by the TerraSAR-X add-on for Digital Elevation Measurements mission. Due to the large along-track separation between the two satellites during the approaching maneuver and the Earth's rotation, useful interferometric acquisitions were only possible at high latitudes. This resulted in a crossing angle between the ground tracks whose impact was corrected by acquiring the two synthetic-aperture radar images with an opposite squint. The still very large 2-km cross-track baseline resulted in a 3.8-m interferometric height of ambiguity, producing extremely detailed images of the topography of the target area. Results acquired over the October Revolution Island, Russia, are shown and discussed.
DLR Import::2019-04-02
Keywords: Digital elevation models; radar interferometry; synthetic aperture radar